Fecal microbiota transplantation: a novel strategy for treating Alzheimer’s disease - Xiang, Wu; Xiang, Han; Wang, Junyu; Jiang, Yiqin; Pan, Chuanhui; Ji, Bingjin; Zhang, Anren (Frontiers in Microbiology, 2023)
Alzheimer's disease is a common neurological disorder, which has become one of the major factors affecting human health due to its serious impact on individuals, families and society. It has been confirmed that gut microbiota can affect the occurrence and development of Alzheimer's disease. Especially, fecal microbiota transplantation plays a positive role in the treatment of Alzheimer's disease. The mechanisms for improving Alzheimer's disease might include anti-inflammation and regulation of amyloid β-protein, synaptic plasticity, short-chain fatty acids, and histone acetylation. In this mini-review, the relationship between fecal microbiota transplantation and Alzheimer's disease was summarized. It is hoped that fecal microbiota transplantation would play a positive role in the prevention and treatment of Alzheimer's disease in the future.